Religion and Ecology: Environmental Ethics in Maintaining the Food and Energy - Dede Aji Mardani; Imas Siti Masuroh; Wida Pursita; Kustana Kustana (TEMALI : Jurnal Pembangunan Sosial, 2023)
Food and energy are a global concern today due to climate change. Some countries are concerned about maintaining the chain of availability of food and energy supplies for the community, especially with the depletion of food supplies and the need for renewable energy. This study aims to analyze the dependence on food and energy and the religious concept of preserving and maintaining the environmental ethics of the depletion of food supplies and fossil energy for Muslim countries. As a system, Islamic economics is expected to be an alternative solution in the sustainability of maintaining the food and energy supply chain ecosystem, starting from raw materials, processing, certification, distribution, and marketing. The method used is through literature review. The results obtained that Muslim countries can play a role in handling food and energy scarcity, including by breaking away from fossil energy dependence by implementing renewable energy, green and blue economy, increasing production capacity and expanding agricultural areas, and providing agricultural and energy technology transfer, diversifying water products, training, and education in the agricultural sector. Although there are regulations on environmental care, the fact that some countries still ignore environmental preservation and sustainability is evident from a large amount of deforestation, drought, flood disasters, deforestation, changes in forest functions, extinction of flora and fauna ecosystems, and global warming. This shows that the process of maintaining environmental ethics is still not optimal. Serious efforts are needed from various parts of the world towards climate change.